Osnovni naboj in šum - Strnad, Janez (Obzornik za matematiko in fiziko, 2009)
Although noise is an inconvenience in information transmission, direct observation of it enables one to measure some specific quantities. In a simple way some basic equations concerning noise are derived. As an example the measurements of elementary charge by way of noise are considered. These measurements have an interesting history.
Keywords: električni tok; fizika